Cavitand-Functionalized SWCNTs for N-methylammonium Detection - Dionisio, Marco (2012)
Single-walled carbon nanotubes (SWCNTs) have been functionalized with highly selective tetraphosphonate cavitand receptors. The binding of charged N-methylammonium species to the functionalized SWCNTs was analyzed by x-ray photoelectron spectroscopy and confirmed by (31)P MAS NMR spectroscopy. The cavitand-functionalized SWCNTs were shown to function as chemiresistive sensory materials for the detection of sarcosine and its ethyl ester hydrochloride in water with high selectivity at concentrations as low as 0.02 mM. Exposure to sarcosine and its derivative resulted in an increased conductance, in contrast to a decreased conductance response observed for potential interferents such as the structurally related glycine ethyl ester hydrochloride.